P012 Systematic review of HPV test [Invader Technology/Real-Time PCR]. (15th August 2013) - Shin, H; Lee, S; Lee, K; Choi, W; Kim, T; Moon, H; Kim, H; Lee, K; Kim, E
Abstract : Objective: HPV Test [Invader Technology/Real-Time PCR] is a molecular genetic test performed for confirming the presence of infection by detecting 14 types of HPV and additionally, for classifying types 16 and 18 genotypes. Methods: It was assessed using 8 domestic databases including Korea Med and Ovid-MEDLINE, Ovid-EMBASE. 1, 214 works were identified. Of them, animal experimental or studies not published in Korean or English were excluded. Total of 23 literatures composed of 8 literatures for Invader Technology and 15 literatures on Real-Time PCR were included in the final assessment. Two reviewers screened all references independently, for assessing included articles quality and extracted data. Results: Index tests were assessed to be a safe test, since it does not impart direct harm to the patients as it is conducted outside the patients body by collecting uterus cervical cells. Effectiveness was assessed by diagnostic accuracy, concordance rate, detection rate. Diagnostic accuracy of Invader Technology with sequencing was high (sensitivity=0.89, specificity=0.92). As the result of comparison between Invader Technology and Hybrid Capture 2(HC2), the false positive rate of index test (5.8%) was lower than HC2 (5.5–21.9%). The concordance rate was 83.1%-94.0%. Diagnostic accuracy of Real-Time PCR with DNA chip was high level (sensitivity=0.96, specificity=1.00). Rate of concordance between Real-Time PCR and HC2 was in the range of 82.6–98.3%, with DNA chip was in the range of 66.7–98.3%. Conclusion: These tests are safety. Also, there are the effectiveness of additional diagnosis for genotypes 16 and 18, high level of concordance with the existing tests and high level of detection of HPV genotypes 16 and 18 in high risk group.